2020
DOI: 10.2147/prbm.s255631
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diabetes-Related Distress and Depression in Saudis with Type 2 Diabetes</p>

Abstract: Objective: This study aims to assess the prevalence of diabetes mellitus (DM)-related distress and depression and their associated factors in Saudi people with type 2 DM (T2DM) in Jazan, Saudi Arabia. It also aims to assess the association between glycemic control and DM-related distress and depression. Methods: This is an analytical, cross-sectional study which recruited 300 Saudi patients with T2DM randomly from primary healthcare centers in Jazan, Saudi Arabia. DM-related distress and depression were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 27 publications
8
36
2
Order By: Relevance
“…In the present study the overall prevalence of DRD among the participants was 118 (36.8%) in which the majority (101; 31.5%) were in moderate distress on a DDS-17 scale. This finding is relatively high in comparison with previous studies conducted in India (13.3%), 37 the Netherlands, 20 Taif, Saudi Arabia (25%), 38 Jazan, Saudi Arabia (22.3%) 15 and Thailand (8.9%). 34 The higher prevalence in the present study could be due to poor quality of diabetes care service, lower level of education, the measurement tool used to quantify the level of diabetic distress, and other forms of stressors.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…In the present study the overall prevalence of DRD among the participants was 118 (36.8%) in which the majority (101; 31.5%) were in moderate distress on a DDS-17 scale. This finding is relatively high in comparison with previous studies conducted in India (13.3%), 37 the Netherlands, 20 Taif, Saudi Arabia (25%), 38 Jazan, Saudi Arabia (22.3%) 15 and Thailand (8.9%). 34 The higher prevalence in the present study could be due to poor quality of diabetes care service, lower level of education, the measurement tool used to quantify the level of diabetic distress, and other forms of stressors.…”
Section: Discussioncontrasting
confidence: 67%
“…The tool is a widely used and well-validated 17-item questionnaire that measures different diabetes related stressors. 13 , 15 Each question has six answer choices: 1 – no problem, 2 – slight problem, 3 – moderate problem, 4 – somewhat serious problem, 5 – a serious problem and 6 – a very serious problem. The questionnaire contains four domains: Emotional Burden (5 items: questions 1, 3, 8, 11, and 14); Physician related distress (4 items: questions 2, 4, 9, and 15); Regimen related distress (5 items: questions 5, 6, 10, 12, and 16); and Interpersonal related distress (3 items: questions 7, 13, and 17).…”
Section: Methodsmentioning
confidence: 99%
“…This case–control study was conducted on Saudi patients with COVID-19 in Jazan Region, located in southwestern Saudi Arabia and characterized by a relatively homogenous population with similar ethnic and socioeconomic characteristics [ [10] , [11] , [12] , [13] , [14] ].…”
Section: Methodsmentioning
confidence: 99%
“…One group aimed to assess the prevalence of T2DM-related distress, glycemic control, and association with depression and their related factors in Jazan, Saudi Arabia. After adjusting for covariates, they found that female sex, age of <45 years, physical inactivity, DM duration of <5 years, and smoking were significantly associated with DM-related distress and depression [ 40 ]. Another study investigated the prevalence of generalized anxiety disorder (GAD) in Taiwanese patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%